Evaluasi E-Court Sebagai Solusi Modernisasi Layanan Perkara Perdata: Kasus Pengadilan Negeri Metro - Anggraini, Selvi; Firmansyah, Firmansyah (Wajah Hukum, 2025)
Metro District Court is one form of public service that serves criminal and civil law issues. The form of public service needs to provide satisfaction to the community who need its services. The court innovates its services by using the E-Court system as a service in civil cases. The innovation of the E-Court system service is intended to improve services to the community. This study aims to evaluate the E-Court system as a service for civil cases at the Metro District Court. The method used is a qualitative approach with a descriptive research design. The types of data used in this study are primary data from interviews conducted with informants including judges, lawyers, court staff and the parties involved. Meanwhile, secondary data sources used in this study come from legal documents, reports related to E-Court. The data analysis used in this study is carried out with a descriptive approach to explain the data systematically according to the phenomenon being studied. The E-Court system can be said to be effective in supporting the Metro District Court in providing services to the public in civil cases. This can be seen from the timeliness process provided by the system in providing services where the system will provide fast service at a low price and can ensure that cases are handled properly. The existence of an E-Court system can support employees in improving the quality of service to the public by providing satisfactory service. Recommendations for further research include expanding similar technology to other types of cases and continuous evaluation of factors that influence the acceptance and implementation of technology in the justice system.